Management of child behavior and oral health in the waiting room: an experience report (Research, Society and Development, 2020)
This article is consolidated as an experience lived by dentistry students of the Federal University of Campina Grande, Patos Campus - PB, in the Extension Program "smile heroes: humanizing looks for a rescue of attitudes". The objective was to highlight the importance of the Dentist and academics in the behavioral improvement of children during clinical care, as well as the need for clinical behavioral management during the waiting of the dental service. The experience was carried out with children aged between 1 and 13 years, who attended the Clinic School of Dentistry of UFCG for care in Pediatric Dentistry and Orthodontics, applying playful activities and lectures during the children's stay in the waiting room and accompanying them in the care. During the project, it was noted the improvement of the behavior of children in the performance of clinical procedures, as well as their confidence with the Dentist and oral hygiene care. In short, it was possible to recognize that the experience allowed extensionists a new look at oral health education, supported by the practices developed with children, in order to understand ways and scenarios of action that renew the exercise of the educational process in health, with a view to overcoming specific and linear care practices.